Development of Active-Smart Packaging: Effect of Chitosan Nanofiber, Zinc Oxide Nanoparticles, and Anthocyanin on Gelatine-Based Halochromic Film for Meat Preservation - Kusumawati, Nita; Bahar, Asrul; Basukiwardojo, Maria Monica Sianita; Samik, Samik; Rahayu, Nunik Tri; Estiningtyas, Indri Wasa; Kurniawan, Muhammad Ridho Hafid (Journal of Engineering and Technological Sciences, 2025)
Gelatine-based smart active packaging has the potential to improve the quality of packaged meat and monitor its freshness without having to open it. This research aims to develop halochromic films by combining gelatine films with chitosan nanofibers (CHNF) and zinc oxide nanoparticles (ZnONPs). The addition of nanofillers such as CHNF and ZnONPs has been proven to improve mechanical properties (The humidity decreased by approximately 15.6%, while Young’s modulus increased tenfold) and provide active packaging properties, such as antioxidants (IC50 test decreased 13% from 33,12191 to 28,82021) and antimicrobials against S. aureus (increased from 9,40 to 19.73 for inhibition zone), E. coli (increased from 6.61 to 19.91 of inhibition zone), and P. aeruginosa (increased from 8.63 to 18.65 of inhibition zone). Meanwhile, the smart packaging properties are provided by anthocyanin from telang flowers, which can change color as the freshness of the meat decreases or the acidity of the meat changes. The quality of smart active packaging is reflected in the pH sensitivity, ammonia release, and anthocyanin release. The film's mechanical properties also showed improvement in humidity, Young's modulus, water vapor permeability (WVP), and water solubility. Fourier Transform Infra-Red (FTIR) characterization analysis showed good compatibility between the gelatine, anthocyanins, CHNF, and ZnONPs matrix. This research result demonstrates that gelatine-based films with a combination of CHNF and ZnONPs can be used to create eco-friendly and multifunctional packaging films for meat preservation.